2022
DOI: 10.1155/2022/7450514
|View full text |Cite
|
Sign up to set email alerts
|

α-Lipoic Acid Strengthens the Antioxidant Barrier and Reduces Oxidative, Nitrosative, and Glycative Damage, as well as Inhibits Inflammation and Apoptosis in the Hypothalamus but Not in the Cerebral Cortex of Insulin-Resistant Rats

Abstract: The research determined the role of α-lipoic acid (ALA) in reducing the brain manifestations of insulin resistance. The mechanism of ALA action is mainly based on its ability to “scavenge” oxygen free radicals and stimulate biosynthesis of reduced glutathione (GSH), considered the most critical brain antioxidant. Although the protective effect of ALA is widely documented in various diseases, there are still no studies assessing the influence of ALA on brain metabolism in the context of insulin resistance and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 125 publications
1
6
0
Order By: Relevance
“…This concept supports our hypothesis that IR is associated with increased expression of S100B in the brain. These mechanisms are proposed to explain the brain's IR pathophysiology and development [47]. In this study, increased expression of cerebral S100B was also detected at the protein level, as revealed by immunohistochemical examination, following the same expression pattern at the molecular level.…”
Section: Discussionsupporting
confidence: 64%
“…This concept supports our hypothesis that IR is associated with increased expression of S100B in the brain. These mechanisms are proposed to explain the brain's IR pathophysiology and development [47]. In this study, increased expression of cerebral S100B was also detected at the protein level, as revealed by immunohistochemical examination, following the same expression pattern at the molecular level.…”
Section: Discussionsupporting
confidence: 64%
“…As a result of Amadori rearrangement, early products of protein glycation (APs, KN, NFK, and DT) are formed ( 45 ). Degradation of APs and the subsequent oxidation, dehydration, polymerization, and condensation leads to the formation of late protein glycation products (including βA and AGEs) ( 46 , 47 ). During these reactions, ROS are also produced that modify amino acids, transform prosthetic groups of proteins, and induce their fragmentation or aggregation ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that both ALA and other compounds containing H 2 S activate K ATP channels, which in turn activate antioxidant and anti-inflammatory pathways, leading to organ protection [ 79 81 ]. It is also possible that the activation of antioxidant and anti-inflammatory pathways by ALA may be via other mechanisms besides its interaction with K ATP channels such as activation of the transcription factor nuclear erythroid 2-related factor 2 (Nrf2; a regulator of transcription of antioxidants and other cytoprotective genes) as well as inhibition of nuclear factor-kappaB (NF-κB; a major protein complex that mediates inflammation by influencing pro-inflammatory cytokine production) and inhibiting the phosphorylating action of mitogen-activated protein kinase (MAPK; another major pro-inflammatory mediator) [ 82 , 83 ]. Other studies also reported anti-fibrotic effect of ALA and H 2 S in animal models of hepatic fibrosis including diabetic animals by inhibiting the expression of the fibrotic proteins, transforming growth factor-beta1 (TGF-β1) and alpha-smooth muscle actin (α-SMA) [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%